Analysis of heat gain against cooling capacity at occupied building - Koh, Kelvin (2009)
This project is carried out to indentify whether the existing cooling capacity is suffice for an occupied building. The first objective of this project is to determine the heat gain of Block W when it’s fully occupied. The second objective of this project is to compare the calculated heat gain against the existing cooling capacity. In this project, Block W, UMP was chosen as the case study. The floor plan of Block W is first studied to review the building specifications. The building specification is used in the calculation of heat gain, and therefore to identify the cooling load required for Block W. When Block W is fully occupied, the number of occupant will be around 1500 people. There are two types of air-conditioning system used in Block W which are split unit and air handling unit and the total existing cooling load is observed to be 852.74 kW. The peak heat gain is calculated as 1172.43 kW using Cooling Load Factor/ Cooling Load Temperature Difference (CLF/CLTD) method at 3pm. Therefore, the existing cooling load is observed to be undersized in design. However, the peak heat gain will only happen occasionally throughout the year. In order to overcome the undersized design cooling capacity problem, the cooling capacity should increase 27.3%.